Report on the To.Sca.Lat.-1.0 Summer School, total scattering analysis for nanoscience in Latin America. Issue 2 (June 2019) - Campos, C. E. M.; Ulbrich, K. F.; Leoni, M.; Masciocchi, N.; Bertolotti, F.; Guagliardi, A.
Abstract : Advanced courses in Applied Crystallography for Nanosciences are not often delivered in Academia and, consequently, require the organization of events specifically tailored to PhD students, postdocs, and young researchers at the very beginning of their scientific careers.